1999
DOI: 10.1029/1998ja900107
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian analysis of two hemisphere observations of galactic cosmic ray sidereal anisotropies

Abstract: We have analyzed the yearly averaged sidereal daily variations in the count rates of 46 underground muon telescopes by fitting Gaussian functions to the data. These functions represent the loss cone and tail‐in anisotropies of the sidereal anisotropies model proposed by Nagashima et al. [l995a, b]. The underground muon telescopes cover the median rigidity range 143–1400 GV and the viewing latitude range 73°N–76°S. From the Gaussian amplitudes and positions we have confirmed that the tail‐in anisotropy is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
5
42
1
Order By: Relevance
“…Large-scale anisotropies and smaller scale excess regions have been detected in the distribution of CRs in this energy range (Nagashima et al 1998;Hall et al 1999;Abdo et al 2008;Abbasi et al 2011;Surdo & Argo-Ybj Collaboration 2011). It has been suggested that the Sun is located in a magnetic flux tube in the ISM, and that such a structure would be a conduit for GCRs (Frisch 1997).…”
Section: Galactic Cosmic Rays and The Local Ismfmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale anisotropies and smaller scale excess regions have been detected in the distribution of CRs in this energy range (Nagashima et al 1998;Hall et al 1999;Abdo et al 2008;Abbasi et al 2011;Surdo & Argo-Ybj Collaboration 2011). It has been suggested that the Sun is located in a magnetic flux tube in the ISM, and that such a structure would be a conduit for GCRs (Frisch 1997).…”
Section: Galactic Cosmic Rays and The Local Ismfmentioning
confidence: 99%
“…The blue open circle gives the ISMF direction derived from the center of the IBEX Ribbon arc. The large blue circular region (light gray) shows the location of the tail-in anisotropy for ∼500 GeV GCRs modeled by Hall et al (1999), with the extent defined by the 68 • width from Nagashima et al (1998). The regions outlined by thick black lines show the observed heliotail that is deflected ∼44 • to the west of the downwind gas direction (red triangle) and is prominent in maps of the globally distributed ENAs (Schwadron et al 2011).…”
Section: Cmb Dipole Anisotropy and The Local Ismfmentioning
confidence: 99%
See 1 more Smart Citation
“…Above the energy range where cosmic rays are directly affected by inner heliospheric processes (see, e.g., Florinski et al 2013;Manuel et al 2014;Florinski et al 2015), a statistically significant anisotropy has been observed by a variety of experiments, sensitive to different energy ranges (from tens of GeV to a few PeV), located on or below the Earth's surface in the northern hemisphere (Nagashima et al 1998;Hall et al 1999;Amenomori et al 2005Amenomori et al , 2006Guillian et al 2007;Abdo et al 2009;Aglietta et al 2009;Zhang et al 2009;Munakata et al 2010;Amenomori et al 2011;de Jong et al 2011;Cui et al 2011;Bartoli et al 2015) and in the southern hemisphere (Abbasi et al 2010a(Abbasi et al , 2011a(Abbasi et al , 2012bAartsen et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al, 1981Mori et al, , 1989Mori et al, , 1993 and at Poatina (42 • S), (Hall et al, 1998(Hall et al, , 1999. Fig.…”
Section: Ga and Ta Of Three Kinds Of Sidereal Anisotropy In The Hmsmentioning
confidence: 99%